The Role of Diabetes and Hyperglycemia on COVID-19 Infection Course—A Narrative Review - Tzeravini, Evangelia; Stratigakos, Eleftherios; Siafarikas, Chris; Tentolouris, Anastasios; Tentolouris, Nikolaos (Frontiers in Clinical Diabetes and Healthcare, 2022)
It was previously reported that subjects with diabetes mellitus (DM) are more vulnerable to several bacterial or viral infections. In the era of coronavirus infectious disease 2019 (COVID-19) pandemic it is reasonable to wonder whether DM is a risk factor for COVID-19 infection too. It is not yet clear whether DM increases the risk for contracting SARS CoV-2or not.However, when patients with DM are infected, they are more likely to develop severe or even fatal COVID-19 than patients without DM. Certain characteristics of DM patients may also deteriorate prognosis.On the other hand, hyperglycemia per se is related to unfavorable outcomes, and the risk may be higher for COVID-19 subjects without preexisting DM.In addition, individuals with DM may experience prolonged symptoms, need readmission, or develop complications such as mucormycosis long after recovery from COVID-19; close follow up is hence necessary in some selected cases. We here present a narrative review of the literature toset light into the relationship between COVID-19 and DM/ hyperglycemia.